Nuevas adiciones a la flora del estado Cojedes, Venezuela. Parte VI. / New additions to the flora of the state of Cojedes, Venezuela. Part VI - Delascio-Chitty, Francisco (Anartia, 2020)
RESUMEN Se presenta una lista de 20 especies de plantas herborizadas en diferentes localidades del estado Cojedes, Venezuela, las cuales constituyen nuevos registros para la flora de la referida entidad. ABSTRACT A list of 20 plant species collected in different localities of the state of Cojedes, Venezuela is given. All of them are new records for the flora of this entity.